1997
DOI: 10.1038/bjc.1997.37
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and collagen IV subunit distribution in normal and neoplastic tissues of colorectum and breast

Abstract: Summary To invade and metastasize, carcinomas must penetrate or lose their epithelial basement membrane (EBM), and then penetrate basement membranes (BMs) surrounding blood vessels, lymphatics, nerves and muscle cells. Knowledge of the composition of different BMs is necessary, so that appropriate antibodies and DNA probes are used to analyse these events. Laminin and type IV collagen are the principal BM components. However, recent studies show these two proteins exist in various isoforms, each of which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 20 publications
3
59
0
1
Order By: Relevance
“…Yet, its precise involvement in tumorigenicity and metastasis is not clearly elucidated as data from the literature are somewhat controversial. On 1 hand, colorectal cancer malignancy has been correlated with decreased or interrupted immunostaining of all basement membrane components at the tumor cell/fibroblasts interface, 12,14,[33][34][35] due either to deficiency in their production or to their degradation by specific proteases. On the other hand, when reconstituted basement membrane (Matrigel) or extracted laminin-1 has been coinjected in animals with various human or murine tumor cell lines, both the incidence and the growth of tumors were increased; 17,36 -39 in these types of experiments, the possibility that growth factors were copurified with the basement membrane components cannot be discarded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, its precise involvement in tumorigenicity and metastasis is not clearly elucidated as data from the literature are somewhat controversial. On 1 hand, colorectal cancer malignancy has been correlated with decreased or interrupted immunostaining of all basement membrane components at the tumor cell/fibroblasts interface, 12,14,[33][34][35] due either to deficiency in their production or to their degradation by specific proteases. On the other hand, when reconstituted basement membrane (Matrigel) or extracted laminin-1 has been coinjected in animals with various human or murine tumor cell lines, both the incidence and the growth of tumors were increased; 17,36 -39 in these types of experiments, the possibility that growth factors were copurified with the basement membrane components cannot be discarded.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, perturbations in the production, deposition and degradation of matrix molecules, among which are laminins, have been observed. [12][13][14][15][16] The role of laminin-1 in tumor growth and metastasis has been evaluated in several cell systems. In particular, it was shown that coinjection of purified laminin-1 and of lung or colon cancer cells increases the growth of the tumors developed as xenografts in nude mice; such an effect was not observed when collagen IV, another basement membrane molecule, was used.…”
Section: Abstract: Laminins; Basement Membrane; Colonic Cancer Cellsmentioning
confidence: 99%
“…Another family of ECM molecules that requires further study in this context is that of the collagen IV isoforms. Their expression has been shown to be regulated independently of laminins in both normal and neoplastic gut (Perreault et al 1998;Hewitt et al 1997).…”
Section: Donaldmentioning
confidence: 99%
“…Magnifications: A ϫ100; B ϫ250; C ϫ200. Vermeulen et al 1995;Hewitt et al 1997). Consequently, these vessels do not fit well into the usual classification of arterioles, capillaries, or venules.…”
Section: Discussionmentioning
confidence: 99%